Benefits of using blended waste coarse lightweight aggregates in structural lightweight aggregate concrete - Aslam, M.; Shafigh, Payam; Jumaat, Mohd Zamin; Lachemi, M. (Elsevier, 2016)
The use of industrial waste as construction material to build environmentally sustainable structures has several practical and economic advantages. Oil palm shell (OPS) is a solid waste material from the palm oil industry that has been successfully used to produce high strength durable lightweight concrete. However, this concrete is very sensitive to a poor curing environment. Therefore, to produce a cleaner and greener concrete, this study used two waste materials from the palm oil industry as coarse aggregate; OPS aggregates were partially replaced with oil-palm-boiler clinker (OPBC) aggregates from 0 to 50% in OPS lightweight aggregate concrete. Properties including workability, density, compressive strength under eight different curing conditions, splitting tensile and flexural strengths, modulus of elasticity and water absorption of green lightweight concrete were measured and discussed. The results show that it is possible to produce environmentally-friendly and high strength structural lightweight aggregate concrete by incorporating high volume waste lightweight aggregates from the palm oil industry.